2016
DOI: 10.1038/srep30502
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E δ-tocotrienol triggers endoplasmic reticulum stress-mediated apoptosis in human melanoma cells

Abstract: Malignant melanoma is the leading cause of death from skin cancer. Drug toxicity and resistance represent a serious challange for melanoma treatments. Evidence demonstrates that natural compounds may play a crucial role in cancer prevention, growth and progression. Vitamin E tocotrienols (TT) were shown to possess antitumor activity. Here, we analyzed the effects of δ-TT on melanoma cell growth and the involvement of the endoplasmic reticulum (ER) stress in this activity. The experiments were performed on huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 59 publications
3
61
0
Order By: Relevance
“…The anti-neoplastic effects of T3 have been extensively studied using tumor cells of mammary gland [351][352][353][354][355][356], lung [357][358][359][360][361][362], liver [363][364][365][366][367] pancreas [368], prostate [362,[369][370][371][372], cervix [373,374], skin [362,[375][376][377], brain [357][358][359]378], stomach [379], and colon [378,380]. Besides that, T3 tends to accumulate in the liver and pancreatic tissues as well as tumor tissues with an unknown mechanism [367,381].…”
Section: Effects Of Tocotrienol On Cancersmentioning
confidence: 99%
“…The anti-neoplastic effects of T3 have been extensively studied using tumor cells of mammary gland [351][352][353][354][355][356], lung [357][358][359][360][361][362], liver [363][364][365][366][367] pancreas [368], prostate [362,[369][370][371][372], cervix [373,374], skin [362,[375][376][377], brain [357][358][359]378], stomach [379], and colon [378,380]. Besides that, T3 tends to accumulate in the liver and pancreatic tissues as well as tumor tissues with an unknown mechanism [367,381].…”
Section: Effects Of Tocotrienol On Cancersmentioning
confidence: 99%
“…The extrinsic and intrinsic pathways are two well-studied mechanisms that contribute to the execution of apoptosis (Figure 1; [10,11,12,13,14,15]). The binding between death ligands, including Fas ligand (Fas L), tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL), and TNF-α, and corresponding death receptors result in the assembly of death-inducing signaling complexes which initiate the extrinsic pathway by activating caspase-8 [23].…”
Section: Overview Of Apoptosismentioning
confidence: 99%
“…Depending on the environmental stress or cell types, apoptosis is differentially executed through extrinsic and intrinsic pathways [10,11]. The intrinsic pathway is activated in the presence of numerous intracellular stimuli, including DNA damage, endoplasmic reticular stress, oxidative stress, and breakage of mitochondrial membranes [12,13]. Activation of multiple death receptors or the withdrawal of cytokines induces extrinsic pathway-mediated apoptosis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Such opposing effects of either increase or decrease of ROS by resveratrol, depending on its concentration, have been observed by Olas, B et al in blood platelets . Recently it has been shown that the δ−TOCO exerts a significant proapoptotic activity on human melanoma cells (while sparing normal melanocytes), both in vitro and in vivo, and that this activity is mediated, at least partially, by the induction of the ER stress process . Even rMnSOD seems exert the oncotoxic activities on various cell lines by increasing the levels of oxidizing substances .…”
Section: Discussionmentioning
confidence: 99%